Emotional Intelligence, Perceived Academic Self-Efficacy, and Perfectionistic Automatic Thoughts as Predictors of Aesthetic-Musical Awareness in Late Adolescence - Esteve-Faubel, Rosa Pilar; Aparicio-Flores, María Pilar; Cavia-Naya, Victoria; Esteve-Faubel, José María (Frontiers in Psychology, 2021)
Aesthetic-musical awareness demarcates a person's own perception of their ability to connect with music and the emotions it evokes. This may imply a benefit for the affective state of the individual. Therefore, the aim of this study was to observe whether there are statistically significant differences in emotional intelligence, perceived academic self-efficacy, and perfectionistic automatic thoughts when there are high and low scores in aesthetic-musical awareness in late adolescence. Likewise, we also aimed to determine whether emotional intelligence, perceived academic self-efficacy, and perfectionistic automatic thoughts are predictors of high aesthetic-musical awareness. To this end, a sample of 798 Spanish students between 17 and 23 years of age (Mage = 18.5 years) was used. Statistically significant differences were found for the dimensions of each variable when there were high and low scores in aesthetic-musical awareness (scores between d = −0.31 and −0.40), with higher mean scores for emotional intelligence, perceived academic self-efficacy, and perfectionistic automatic thoughts being present in the group with high aesthetic-musical awareness. Likewise, it was observed that the probability of presenting high scores in aesthetic-musical awareness was higher when there was an increase in emotional intelligence, perceived academic self-efficacy, and perceived automatic thoughts. In conclusion, the results found demonstrate that both emotional intelligence, perceived academic self-efficacy, and the presence of perfectionistic automatic thoughts influence on whether an individual has greater aesthetic-musical awareness. Taking into account previous studies that show how music influences the well-being of the person, these findings show a favorable link for the design of programs that benefit the emotional state of adolescents.